Deciphering Corporate Governance and Environmental Commitments among Southeast Asian Transnationals: Uptake of Sustainability Certification - Roda, J.M.; Kamaruddin, N.; Tobias, R.P. (MDPI, 2015)
Promoting tropical forest sustainability among corporate players is a major challenge. Many tools have been developed, but without much success. Southeast Asia has become a laboratory of globalization processes, where the development and success of agribusiness transnationals raises questions about their commitment to environmental concerns. An abundance of literature discusses what determines the behavior of Asian corporations, with a particular emphasis on cultural factors. Our hypothesis is that financial factors, such as ownership structure, may also have a fundamental role. We analyzed the audited accounts of four major Asian agribusiness transnationals. Using network analysis, we deciphered how the 931 companies relate to each other and determine the behavior of the transnationals to which they belong. We compared various metrics with the environmental commitment of these transnationals. We found that ownership structures reflect differences in flexibility, control and transaction costs, but not in ethnicities. Capital and its control, ownership structure, and flexibility explain 97% of the environmental behavior. It means that existing market-based tools to promote environmental sustainability do not engage transnationals at the scale where most of their behavior is determined. For the first time, the inner mechanisms of corporate governance are unraveled in agricultural and forest sustainability. New implications such as the convergence of environmental sustainability with family business sustainability emerged.